The Relationship of Motivation and Job Satisfaction of School Principal at the State Junior High School in Karawang Regency - Herlina, Herlina; Mayasari, Linda Ika; Desi, Sukma (Jurnal Ilmiah Peuradeun, 2017)
The objective of this research was to determine the Relationship between Motivation and Job Satisfaction of Principal at The State Junior School in Karawang. In doing the research, it has been conducted by using quantitative approach with the method of survey and corelational technique. The data were collected through participant observation using survey by questionnaires. The data analysis using simple correlation and simple linear regression. The target population size of this research is 85 of Principal. Research samples selected as many as 57 principals using simple random sampling technique. Based on this research of data obtained the following conclusions: The motivation has positive relationship to job satisfaction, the job satisfaction can be improved by increasing the motivation.